NIC: Colposcopy and directed biopsy in the diagnosis of early cervical lesions - Rengifo, Eduardo (2015)
OBJECTIVES. To divulge colposcope use and indications in gynecological consultation, and its usefulness with abnormal smears and in the early diagnosis of both cervical intraepithelial neoplasia (CIN) and preclinical cancer. DESIGN. Prospective study of 247 cases of CIN. SETTING. A Loayza Hospital, Lima, Perú. RESULTS. CIN I was present in 72 cases, CIN II in 73 and CIN III in 102. Higher incidence was in 30-34 year-old (19%), followed by 25-29year-old (14,6%) and 35-39 year-old (13,8%); 72% started sexual life before age 20 and 36,8% had 2 or more sexual partners. Aspathology accentuates, diagnosis is more evident and CIN III reaches a colposcopy histology correlation of 94%. CONCLUSIONS. CIN is found at early ages. Any positive cytology should befollowed by colposcopy guided biopsy. Colposcopy along with cytology and biopsy efficiently diagnose early lesions of the uterine cervix and lead to early treatment.